The Improvement of Studentsâ Learning Outcomes With the Implementation of Cooperative Learning Model Think-Talk-Write (TTW) at the X1 Grade of State Senior High School 1 Kampar Kiri in Academic Year 2014/2015 - Mulyani, Mulyani (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The research was classroom action research applied to students of State Senior High School 1 Kampar Kiri grade X1 which amounted to 32 people. The objective of theresearch was to improve studentsâ learning outcomes grade X1 with the application of cooperative learning model Think-Talk-Write (TTW) done in two cycles. The cooperative learning of Think-Talk-Write(TTW) was introduced by Huinker & Laughlin. Basically this learning was built through the process of thinking, speaking and writing. Think-Talk-Write (TTW) learning could grow problem-solving skills. The learning process of Think-Talk-Write (TTW) was conducted in groups of 3-5 students in each group. In this group students were asked to read, make small notes, explain, listen and share ideas with friends and then express it through writing.Think-Talk-Write (TTW) learning process. The results showed that an increase in studentsâ learning outcomes which seen from the absorption and mastery of studentsâ learning grade X1 State Senior High School 1 Kampar Kiri. Absorption rate increased by 5%, while the learning mastery of students increased by 15.13%. Thus, a classroom action research using Think-Talk-Write (TTW) cooperative learning model could improve studentsâ learning outcomes grade X1 of State Senior High School 1 Kampar Kiri.